Correction of renal dysfunction under the influence of dietary management, exercises and lisinopril in patients with abdominal obesity and hypertension. - M. K. Rokutova (Medičnì Perspektivi)
The purpose of research is to assess the impact of diet therapy, physical activity and an ACE inhibitor (lisinopril) on renal dysfunction in patients with abdominal obesity and hypertension. The study involved 14 patients with abdominal obesity, 2-3 degrees in BMI, hypertension, I-II stage, 1 degree, and severe insulin resistance. Men were 9 (64.3%) patients, women - 5 (35.7%) persons. The average age of the patients was 37,0±1,7 years, mean BMI - 44.7 [35.5; 46.5] kg/m2. BP was between 140-158/90-98 mm Hg. Diroton (lisinopril, Richter Gedeon Ltd, Hungary) was administered 1 time per day in the morning at a dose of 10 mg. The effect of diet therapy, exercise and lisinopril on parameteres of renal function (glomerular filtration rate, urine protein, urine albumin, urine β2 microglobulin, urine albumin / creatinine ratio, β2- microglobulin  / urine creatinine ratio). After 6 months of treatment there was a significant decrease in body weight (p<0.001) from 123.5 [110.0; 154.0] to 120.0 [105.0; 142.0] kg, with a BMI from 44.7 [35.5; 46.5] to 42.7 [33.9; 45.2] kg/m2 (p <0.001) and waist from 118.0 [105.0; 142.0] to 116.0 [105.0; 135.0] cm (p<0.05). Normalization of blood pressure was achieved in 71,4% (n=10) patients and a significant decrease in blood pressure - in 28,7% (n=4) persons in the 6th week of treatment. The level of GFR was significantly (p<0.01) decreased from 202.2 [156.1; 254.6] to 200.3 [148.8; 220.6] ml/min, the level of β2-mg decreased from 3.4 [1.1, 4.8] to 2.8 [1.4; 3.6] mg/24 h, the β2-mg / Cr urine ratio - from 2.3 [0.9, 4.0] to 1.9 [1.0, 2.7] mg/g, which is a positive point prognosis of obesity-associated nephropathy in these patients. GFR normalized in 2 (14.3%) patients, β2-mg and β2-mg / Сr ratio - only in 1 (7.1%) patients. GFR decreased in 10 (71.4%) patients, β2-mg and β2-mg / Cr ratio – in 12 (85.7%) patients. It is the result of complex treatment of diet, exercises and lisinopril. A significant reduction (p<0.01) of leptin from 95.6 [58.1; 141.9] to 87.0 [56.5; 132.6] ng/ml was observed in 13 (92.9%) patients. Patients in this group showed a significant decrease in lipid, carbohydrate metabolism and the level of insulin resistance. ACE inhibitors in combination with diet and exercises considering metabolic disorders are the complex treatment early manifestations of kidney damage in patients with abdominal obesity and hypertension.